Labour mobility as an adjustment mechanism to asymmetric shocks in Europe: evidence from the Czech Republic, Hungary, Poland and Slovakia - Dennis Nchor (Journal for Labour Market Research, 2020)
This paper assesses the nature and correlation of shocks in Visegrad countries and investigates the role of labour mobility in the process of adjustment to the effects of asymmetric shocks. Structural vector autoregression (SVAR) models are employed to assess the nature and correlation of shocks while dynamic cointegrated panel autoregressive distributed lag (ARDL) models are used to determine the role of labour mobility in the adjustment process. The dataset for the SVAR models is quarterly time series and covers the period 2000-2020. The dataset for the cointegrated panel ARDL models is annual and covers the period 2000-2019. The results show more asymmetries in external supply, domestic supply, demand and monetary shocks before the financial crisis. The findings also show that more symmetries occurred in Visegrad countries after the financial crisis in relation to external and domestic supply shocks. Asymmetries persisted with regard to demand and monetary shocks after the financial crisis. With labour mobility as an adjustment mechanism to asymmetric shocks, the paper finds that the capacity of labour mobility is very low. The percentage of net migration in the total population is less than 1% in the four countries compared to 15% in the United States. The size of the adjustment coefficients shows that it takes 3-5 years for countries to adjust to asymmetric shocks through labour mobility.
Keywords: F15; F41; J01; J08; J61; 330; Demand shocks; Supply shocks; Symmetry; Asymmetry; Labour mobility